Association of Early MRI Characteristics With Subsequent Epilepsy and Neurodevelopmental Outcomes in Children With Tuberous Sclerosis Complex. (22nd March 2022) - Hulshof, Hanna M.; Kuijf, Hugo J.; Kotulska, Katarzyna; Curatolo, Paolo; Weschke, Bernhard; Riney, Kate; Krsek, Pavel; Feucht, Martha; Nabbout, Rima; Lagae, Lieven; Jansen, Anna; Otte, Wim M.; et al.
Abstract : Background and Objectives: Multiple factors have been found to contribute to the high risk of epilepsy in infants with tuberous sclerosis complex (TSC), including evolution of EEG abnormalities, TSC gene variant, and MRI characteristics. The aim of this prospective multicenter study was to identify early MRI biomarkers of epilepsy in infants with TSC aged <6 months and before seizure onset, and associate these MRI biomarkers with neurodevelopmental outcomes at 2 years of age. The study was part of the EPISTOP project. Methods: We evaluated brain MRIs performed in infants younger than 6 months with TSC. We used harmonized MRI protocols across centers and children were monitored closely with neuropsychological evaluation and serial video EEG. MRI characteristics, defined as tubers, radial migration lines, white matter abnormalities, cysts, calcifications, subependymal nodules (SEN), and subependymal giant cell astrocytoma (SEGA), were visually evaluated and lesions were detected semiautomatically. Lesion to brain volume ratios were calculated and associated with epilepsy and neurodevelopmental outcomes at 2 years. Results: Lesions were assessed on MRIs from 77 infants with TSC; 62 MRIs were sufficient for volume analysis. The presence of tubers and higher tuber-brain ratios were associated with the development of clinical seizures, independently of TSC gene variation and preventive treatment. Furthermore, higher tuber-brain ratios were associated with lower cognitive and motor development quotients at 2 years, independently of TSC gene variation and presence of epilepsy. Discussion: In infants with TSC, there is a significant association between characteristic TSC lesions detected on early brain MRI and development of clinical seizures, as well as neurodevelopmental outcomes in the first 2 years of life. According to our results, early brain MRI findings may guide clinical care for young children with TSC. Classification of Evidence: This study provides Class I evidence that in infants with TSC, there is a significant association between characteristic TSC lesions on early brain MRI and the development of clinical seizures and neurodevelopmental outcomes in the first 2 years of life.